How Does the Change of Information Source Affect Residents’ Risk Attitudes? - Zhang, Shihu; Zhang, Guangcai; Li, Jinpei; Gu, Haiying (Frontiers in Psychology, 2022)
Although many studies have discussed the economic impacts of Internet use, little attention has been paid to the impacts of the Internet as a new information channel on the concepts of residents from a micro perspective. Using the data from the China Family Panel Studies (CFPS), this paper investigates the effects of Internet use on residents’ risk attitudes. Both Generalized Ordered Logit Model and Logit model are used to identify the effects of Internet use. The results show that Internet use, as a new information channel, can significantly improve residents' subjective and objective risk preferences. The heterogeneity analysis also reveals that these impacts are different among groups with different reasons for Internet use and different personal characteristics. Finally, several methods are used to examine the issue of endogeneity in the models. This paper expands the research on the effects of Internet on people's concepts from the micro perspective.